The DNA repair enzyme, aprataxin, plays a role in innate immune signaling - Madsen, Helena B.; Pease, Louise I.; Scanlan, Rebekah-Louise; Akbari, Mansour; Rasmussen, Lene J.; Shanley, Daryl P.; Bohr, Vilhelm A. (Frontiers in Aging Neuroscience, 2023)
Ataxia with oculomotor apraxia type 1 (AOA1) is a progressive neurodegenerative disorder characterized by a gradual loss of coordination of hand movements, speech, and eye movements. AOA1 is caused by inactivation mutation in the APTX gene.APTX resolves abortive DNA ligation intermediates. APTX deficiency may lead to the accumulation of 5'-AMP termini, especially in the mitochondrial genome. The consequences of APTX deficiency includes impaired mitochondrial function, increased DNA single-strand breaks, elevated reactive oxygen species production, and altered mitochondrial morphology. All of these processes can cause misplacement of nuclear and mitochondrial DNA, which can activate innate immune sensors to elicit an inflammatory response.This study explores the impact of APTX knockout in microglial cells, the immune cells of the brain. RNA-seq analysis revealed significant differences in the transcriptomes of wild-type and APTX knockout cells, especially in response to viral infections and innate immune pathways. Specifically, genes and proteins involved in the cGAS-STING and RIG-1/MAVS pathways were downregulated in APTX knockout cells, which suggests an impaired immune response to cytosolic DNA and RNA.The clinical relevance of these findings was supported by analyzing publicly available RNA-seq data from AOA1 patient cell lines. Comparisons between APTX-deficient patient cells and healthy control cells also revealed altered immune responses and dysregulated DNA-and RNA-sensing pathways in the patient cells.Overall, this study highlights the critical role of APTX in regulating innate immunity, particularly in DNA-and RNA-sensing pathways. Our findings contribute to a better 2 This is a provisional file, not the final typeset article understanding of the underlying molecular mechanisms of AOA1 pathology and highlights potential therapeutic targets for this disease.